Basic newborn resuscitation guidelines for healthcare providers in Maragua District Hospital: a best practice implementation project. (July 2018) - Kebaya, Lilian Maureen Nyatichi; Kiruja, Jason; Maina, Michuki; Kimani, Salome; Kerubo, Christine; McArthur, Alexa; Munn, Zachary; Ayieko, Philip
ABSTRACT: Objective: The overall aim of this project was to assess compliance with evidence-based criteria regarding newborn resuscitation among healthcare workers in the maternity units in Maragua District Hospital (a busy district hospital in Kenya). Introduction: Globally, the majority of deaths under five years are attributable to neonatal causes. Perinatal asphyxia accounts for a significant portion of these deaths, especially in developing countries. These deaths are largely preventable, and interventions geared towards assisting newborns to initiate their first breath within the first minute of life have markedly reduced mortality. Methods: This implementation project was conducted in the maternity units of a busy district hospital. Evidence-based audit criteria were developed on the basis of an evidence summary developed by the Joanna Briggs Institute (JBI). Using the JBI Practical Application of Clinical Evidence System software (JBI PACES), a baseline audit was conducted including a sample size of 55 healthcare providers and 300 patient case notes followed by an identification of potential barriers and strategies to overcome them. A follow-up audit including a sample size of 55 healthcare providers was conducted by using the same audit criteria. Results: Improvements in practice were demonstrated in all criteria. The baseline audit demonstrated that three of the five audit criteria were found to be less than 50%, indicating moderate compliance with current evidence with regards to newborn resuscitation. Following implementation of the strategies, which included a six-week education and demonstrative skills training, and updating of the protocols and equipment, there was a significant improvement in all the criteria audited, with the first four criteria achieving 100% compliance, and the fifth criteria achieving 90% compliance. Conclusion: On completion of the project, the participants demonstrated an increase in knowledge and skills on newborn resuscitation, which led to a significant reduction in admission of newborns with birth asphyxia to the newborn unit.